How Does Post-Crisis Bank Capital Adequacy Affect Firm Investment? - Sun, Yangfan (IMF Working Papers; Working Paper ;, 2015)
We examine the effect of bank capital levels on firm investment drawing on a sample of 11,106 non-financial firms from 2007 to 2013 in 16 advanced economies. We examine two measures of bank capital adequacy, the Tier 1 ratio and a simple leverage ratio, and find that firms with larger external financial needs invest relatively more when domestic financial systems have relatively high leverage ratios. This pattern is more pronounced for those firms that have sound fundamentals, suggesting that bank balance sheets and their willingness to extend credit can be an important factor in determining aggregate investment and growth outcomes. The empirical findings are robust to a range of specifications. Bank Tier 1 capital ratio does not appear to have a significant effect on corporate investment, possibly because a higher Tier 1 ratio also captures a high share of assets with low risk weights.